Minangkabau Language Greeting System In Creative Text Works: A Case Study on Modern Indonesian Fiction Minangkabau Local Color and Lyrics of Popular Modern Minangkabau Songs - Hasanuddin W.S. (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
This article contains a discussion of the Minangkabau language greetings in the text of creative work. This discussion is a case study of how the Minangkabau greeting is used in modern Indonesian fiction of the local Minangkabau color and in the text or lyrics of popular modern Minangkabau songs. The word Minangkabau greeting, especially those that are semantic in the text of creative work, is used in certain situations that are closely related to factors of narrative, ethnicity, and kinship. Several types of semantic-style greetings are found in self-names, kinship, traditional titles, educational outcomes, positions, deeds, other greetings, and figures of speech. The use of Minangkabau greeting words in the text of creative works can be viewed positively because the text of creative works has indirectly functioned as (1) the documentation system for naming systems in the Minangkabau language, (2) the maintenance and development media for intangible cultural heritage in the form of Minangkabau language greetings . The maintenance and development of this intangible cultural heritage is important in view of the advances in science and technology, as well as the opening of the globalization stream which allows the tradition of using greetings in the Minangkabau language by the successor generation due to the influence of modernization and the lifestyle of modern (urban) societies.